Simulating the Case against Stock Picking - Higgins, Charles J. (Journal of Accounting, Business and Finance Research, 2018)
In simulating a portfolio of 100 security prices the median terminal price was regularly below that of the average mean portfolio price. In that picking a single security would likely choose the median terminal price, a case can be made against stock picking.